NEU1 Sialidase Regulates Membrane-tethered Mucin (MUC1) Ectodomain Adhesiveness for Pseudomonas aeruginosa and Decoy Receptor Release - Lillehoj, Erik P. (J Biol Chem, 2015)
Airway epithelia express sialylated receptors that recognize exogenous danger signals. Regulation of receptor responsiveness to these signals remains incompletely defined. Here, we explore the mechanisms through which the human sialidase, neuraminidase-1 (NEU1), promotes the interaction between the sialoprotein, mucin 1 (MUC1), and the opportunistic pathogen, Pseudomonas aeruginosa. P. aeruginosa flagellin engaged the MUC1 ectodomain (ED), increasing NEU1 association with MUC1. The flagellin stimulus increased the association of MUC1-ED with both NEU1 and its chaperone/transport protein, protective protein/cathepsin A. Scatchard analysis demonstrated NEU1-dependent increased binding affinity of flagellin to MUC1-expressing epithelia. NEU1-driven MUC1-ED desialylation rapidly increased P. aeruginosa adhesion to and invasion of the airway epithelium. MUC1-ED desialylation also increased its shedding, and the shed MUC1-ED competitively blocked P. aeruginosa adhesion to cell-associated MUC1-ED. Levels of desialylated MUC1-ED were elevated in the bronchoalveolar lavage fluid of mechanically ventilated patients with P. aeruginosa airway colonization. Preincubation of P. aeruginosa with these same ex vivo fluids competitively inhibited bacterial adhesion to airway epithelia, and MUC1-ED immunodepletion completely abrogated their inhibitory activity. These data indicate that a prokaryote, P. aeruginosa, in a ligand-specific manner, mobilizes eukaryotic NEU1 to enhance bacterial pathogenicity, but the host retaliates by releasing MUC1-ED into the airway lumen as a hyperadhesive decoy receptor.